Feasibility of Well Cake and Cookies Business in North Cikarang: Marketing and Cost Perspectives - Lion, Ramlianus; Musliha, Anisa; Nur, Harum; Koesumawati, Shindy; Sheila, Welly; Saputra, Ari (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study aims to analyze the business feasibility of Well Cake and Cookies, a home industry that produces various types of brownies. The research method used was qualitative with descriptive analysis, covering marketing and cost aspects. The results showed that marketing strategies implemented through social media, such as Instagram and WhatsApp, were effective in reaching the target market consisting of young people and cake lovers. Furthermore, product variety and the ability to meet consumer demand are competitive advantages. In terms of costs, initial capital and daily production costs are still within reasonable limits, supporting business continuity. Despite challenges in competition and visibility on digital platforms, Well Cake and Cookies has the potential to grow and achieve optimal profits. With good management and the right marketing strategy, this business is expected to compete effectively in the sweet food market.